Rekonseptualisasi Gerakan Dakwah Jamah Tabligh Kota Palopo - Achmad Sulfikar (Institut Agama Islam Negeri Palopo, 2016)
This study aims to acquire factual knowledge, understanding and expressing a variety of symptoms that arise throughout the process of conveying messages of dakwah by members of Jamaah Tabligh Palopo, and develop concepts, theoretical models, and communication approaches with regard to the role of Jamaah Tabligh as a preacher. Researchers conducted a participant observation of the Jamaah Tabligh Palopo uses dramaturgical theory of Erving Goffman, who use the theater metaphor to analyze human behavior. Through this research, will know what, why and how they're to preach, especially about their impression management in conveying the messages of dakwah. The author found that Jamaah Tabligh is more of a cultural movement, the movement clearly well organized. In the context of dramaturgy there is a clear line between the front stage and back stage, but Jamaah Tabligh give an opportunity to the public to at any time to cross the edge. Actors in this case members of the Jamaah Tabligh tried to play a good role as a preacher, it is dominated by the more spiritual motivation